Effect of electro-activated solutions of sodium acetate and sodium propionate on geosmin producing Streptomyces avermitilis strain. (December 2017) - Liato, Viacheslav; Aïder, Mohammed
Abstract: Electro-activated solutions of salts of weak organic acids are defined as novel potent disinfecting agents that can be used in the agri-food industry. The aim of the present work is to study and understand the destruction mechanism of electro-activated solutions of sodium acetate (EAA) and sodium propionate (EAP) against Streptomyces avermitilis spores. The results of antibacterial activity showed high bacteriostatic effect for all the tested solutions, including sodium hypochlorite used as positive control. Under specific conditions, test on minimal inhibitory concentration demonstrated that the used electro-activated solutions have inhibition activity comparable or higher than the control solution, with the following inhibiting concentrations of 0.004, 0.002 and 0.073 mol/L, for EAA, EAP and NaOCl, respectively. The most active solutions resulted in destruction effect of more than 7 log CFU/mL. The physiological state of the S. avermitilis spores was assessed by transmission electron microscopy after treatments with the electro-activated organic solutions and NaOCl. The results displayed coreless and/or deformed cellular forms with ruptured membranes and released components of spores. The main practical importance of this study is that the targeted final objective is to develop safe and effective alternative to sodium hypochlorite to ensure microbial safety of fresh vegetables under storage conditions. In this context, we studied the potential of electro-activated solutions of sodium acetate and sodium propionate against spores of Streptomyces avermitilis and compared this activity with sodium hypochlorite, the mostly used disinfecting agent in the agri-food industry. Highlights: Streptomyces avermitilis was treated with electro-activated solutions of sodium acetate and sodium propionate. Electro-activated solutions highly active against Streptomyces avermitilis. Electro-activated solutions acted through membrane cell rupture and release of spore components. Electro-activated solutions as alternative to sodium hypochlorite.